2014
DOI: 10.1016/j.neuroimage.2013.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stages and sex differences of white matter and behavioral development through adolescence: A longitudinal diffusion tensor imaging (DTI) study

Abstract: White matter (WM) continues to mature through adolescence in parallel with gains in cognitive ability. To date, developmental changes in human WM microstructure have been inferred using analyses of cross-sectional or two time-point follow-up studies, limiting our understanding of individual developmental trajectories. The aims of the present longitudinal study were to characterize the timing of WM growth and investigate how sex and behavior are associated with different developmental trajectories. We utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
404
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(452 citation statements)
references
References 96 publications
42
404
4
2
Order By: Relevance
“…Several previous studies have found gender differences in structural connectivity (Hänggi et al., 2010; Schmithorst, 2009; Simmonds, Hallquist, Asato, & Luna, 2014), however, a recent DTI study in the current cohort did not show gender differences (Muetzel et al., 2015). Gender differences have also previously been observed in neuroanatomical studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Several previous studies have found gender differences in structural connectivity (Hänggi et al., 2010; Schmithorst, 2009; Simmonds, Hallquist, Asato, & Luna, 2014), however, a recent DTI study in the current cohort did not show gender differences (Muetzel et al., 2015). Gender differences have also previously been observed in neuroanatomical studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Posthoc Student's t tests between genotypes within each age group showed enhanced projections from IL to BLA in adolescent [t(12) = 13.81; P < 0.0001] and adult [t(12) = 12.49; P < 0.0001] FAAH A/A mice relative to FAAH C/C mice but no differences in fiber density in preadolescent mice [t(12) = 0.56; P = 0.583] as a function of FAAH C385A genotype. Prior studies have shown that anxiety disorders peak during adolescence (1, 2) when there are dynamic changes in AEA levels (10, 11) that impact anxiety-related frontolimbic circuitry (28)(29)(30)(31). Moreover, we have shown that the FAAH A385 allele is associated with increased frontolimbic connectivity and lower anxiety in both mice and humans in adulthood (14).…”
Section: Faah C385a-associated (Phenotypic) Differences In Frontolimbmentioning
confidence: 56%
“…Sex differences in white matter integrity as a function of infant diet have not been reported in young children who were term-born. However, sex differences in developmental trajectories of white matter in healthy adolescents, as well as sex differences of white matter in healthy adults, have been previously reported by DTI studies (28,33). Furthermore, a number of studies have shown that effects of infant diet on later growth and development are more prominent in male children.…”
Section: Infants' Diet and White Mattermentioning
confidence: 93%
“…Furthermore, sex differences were found in white matter growth profiles (28), but sex-specific evaluation of diet effects on healthy children (term-born) at school age has not been studied. In this study, we used DTI TBSS to evaluate brain white matter integrity in healthy 8-y-old children who were predominately BF or FF as infants.…”
mentioning
confidence: 99%